2007
DOI: 10.1016/j.febslet.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation of leaf motor cells

Abstract: ''Osmotic Motors'' -the best-documented explanation for plant leaf movements -frequently reside in specialized motor leaf organs, pulvini. The movements result from dissimilar volume and turgor changes in two oppositely positioned parts of the pulvinus. This Osmotic Motor is powered by a plasma membrane proton ATPase, which drives KCl fluxes and, consequently, water, across the pulvinus into swelling cells and out of shrinking cells. Light signals and signals from the endogenous biological clock converge on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
103
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 83 publications
0
103
0
Order By: Relevance
“…Research of motor cells in the pulvini of Mimosa pudica indicated that along with the differentiation of motor cells, the expression of both vacuolar aquaporin and H + -ATPase were increased (FleuratLessard et al, 1997). Furthermore, vacuolar H + -pyrophosphatase and H + -ATPase create the tonoplast electrochemical gradient by pumping H + into the vacuoles, which are important for osmoregulation of motor cells and osmotic adjustment in plants (Moran, 2007).…”
mentioning
confidence: 99%
“…Research of motor cells in the pulvini of Mimosa pudica indicated that along with the differentiation of motor cells, the expression of both vacuolar aquaporin and H + -ATPase were increased (FleuratLessard et al, 1997). Furthermore, vacuolar H + -pyrophosphatase and H + -ATPase create the tonoplast electrochemical gradient by pumping H + into the vacuoles, which are important for osmoregulation of motor cells and osmotic adjustment in plants (Moran, 2007).…”
mentioning
confidence: 99%
“…. 16,17 These results suggest that regulation of these osmotic signaling events including ROS generation requires Ca 2+ influx. However, their molecular basis and regulatory mechanisms have remained poorly elucidated.…”
Section: +mentioning
confidence: 77%
“…Circadian and light-induced leaf movements of several plants are due to changes in turgor pressure in specialized motor cells that are part of flexible hinges (so-called pulvini) located at the base of the stalk of the leaf (Iino et al 2001;Moran 2007). A similar mechanism, but with a rapid movement, is well known for mimosa, which folds its leaves upon external stimuli.…”
Section: (B ) Turgor Pressurementioning
confidence: 99%